Further Results on the Dilogarithm Integral - Biljana Jolevska-Tuneska; Brian Fisher (Journal of Applied Mathematics)
The dilogarithm integral Li(xs) and its associated functions Li+(xs) and Li-(xs) are defined as locally summable functions on the real line. Some convolutions and neutrix convolutions of these functions and other functions are then found.